1994
DOI: 10.1136/bjsm.28.3.153
|View full text |Cite
|
Sign up to set email alerts
|

Massage--the scientific basis of an ancient art: Part 2. Physiological and therapeutic effects.

Abstract: The physiological and therapeutic effects of massage are frequently questioned. This article reviews previous research into the effects of massage on blood flow and composition, oedema, connective tissue, muscle and the nervous system. Although further invetigations are clearly required in certain areas, the discussion demonstrates that the use of massage in sports medicine can be justified according to orthodox scientific criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(143 citation statements)
references
References 25 publications
2
130
0
11
Order By: Relevance
“…The underlying mechanism of the action of massage is not well understood (23) -early research reviewed physiological benefits to include increasing blood flow (24) ; however, more recent studies using Doppler ultrasound techniques have found the use of massage had no effect on venous or arterial blood flow (25) . Following this further, theories that support massage therapy's influence on lymph drainage to remove waste and reduce edema are reflected in anecdotal accounts and empirical evidence, and conclusive research is needed (26) .…”
Section: Atkins and Eichler: Effects Of Self-massage On Knee Osteoarthrmentioning
confidence: 99%
“…The underlying mechanism of the action of massage is not well understood (23) -early research reviewed physiological benefits to include increasing blood flow (24) ; however, more recent studies using Doppler ultrasound techniques have found the use of massage had no effect on venous or arterial blood flow (25) . Following this further, theories that support massage therapy's influence on lymph drainage to remove waste and reduce edema are reflected in anecdotal accounts and empirical evidence, and conclusive research is needed (26) .…”
Section: Atkins and Eichler: Effects Of Self-massage On Knee Osteoarthrmentioning
confidence: 99%
“…The use of lumbar massage systems in automobile seats have also been shown to reduce lower back discomfort [14,15]. It is thought that these interventions reduce discomfort by increasing or maintaining local tissue nutrition [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Massage therapy and occlusal splint usage are employed to stimulate local blood fl ow and the transport of nutrients, reestablish normal muscle status by avoiding hyperactivity and reduce pain [29][30][31][32][33] . Thus, the combination of these two therapies is highly recommended, as demonstrated by the lack of improvement in symptoms in the control group at the fi nal evaluation.…”
Section: Discussionmentioning
confidence: 99%